Integrated control of ticks and tick-borne diseases newsletter - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
lCTTD newsletter Faculty of Veterinary Medicine, Institute of Infectious Disease & Immunology, PO Box 165 3508 TD Utrecht THE NETHERLANDS